Solid-state fermentation by Aspergillus niger and Trichoderma koningii improves the quality of tea dregs for use as feed additives. - Yiyan Cui (Public Library of Science (PLoS), 2021)
This study evaluated the ability of Aspergillus niger and Trichoderma koningii to improve the quality of tea dregs (TDs) through solid-state fermentation as well as the value of the fermented tea dregs (FTDs) produced for use as bio-feed additives. After fermentation, FTDs differed in color and structure. Fermentation with A. niger and T. koningii increased the contents of crude protein, crude fiber, neutral detergent fiber, and acid detergent fiber of TDs. Compared to the unfermented group, the contents of reducing sugar, total flavonoids, total polyphenols, and theasaponins were increased in A. niger FTDs, while in T. koningii FTDs caffeine was completely degraded, the theasaponins were lower, and the contents of reducing sugar and caffeine higher. Regarding free amino acids, A. niger FTDs had the highest content of total amino acids, total essential amino acids, total non-essential amino acids, total aromatic amino acids, total branched-chain amino acids, and total non-protein amino acids, and all types of essential amino acids, followed by T. koningii FTDs and the control TDs. Fungal fermentation had similar effects on the content of various hydrolytic amino acids as those on above free amino acids, and increased the content of bitter and umami components. The composition of essential amino acids of TDs or FTDs was similar to that of the standard model, except for sulfur-containing amino acids and isoleucine. Solid-state fermentation with A. niger and T. koningii effectively improved the nutritional value of TDs, increased the contents of functional substances, and improved the flavor of TDs. This study demonstrated a feasible approach to utilize TDs that not only increases animal feed resources, but also reduces the production of resource waste and pollution.